Cervical single open-door laminoplasty with or without local lateral mass screw fixation and fusion to treat cervical spinal cord injuries accompanied by segmental spinal canal stenosis - Yu, Zihao; Xie, Hongwei; Ouyang, Ziyu; Zhang, Hua (Frontiers in Surgery, 2023)
Study Design: A retrospective study. Objectives: To investigate the efficacy of cervical single open-door laminoplasty with or without local lateral mass screw fixation and fusion in the treatment of cervical spinal cord injury with multi-segmental spinal canal stenosis. Setting: The Second Affiliated Hospital, School of Medicine, Zhejiang University. Methods: Of these patients, 42 were divided into the stable group and underwent cervical single open-door laminoplasty; whereas the other 14 were divided into the unstable group and underwent cervical single open-door laminoplasty combined with lateral mass screw fixation and fusion. The status and improvements of neurological function were evaluated before surgery, at discharge and the final follow-up using American Spinal Cord Injury Association (ASIA) impairment scale and Japanese Orthopedic Association (JOA) score. Results: Improvement of neurological function (AISA impairment scale): 52.5% in the stable group (15 D-grade and 4 A-grade didn’t increase), and 45.5% in the unstable group (3 D-grade and 3 A-grade didn’t increase). The postoperative improvement rate of JOA scores was 19.1 ± 21.6% in the stable group and 18.6 ± 18.4% in the unstable group (p > 0.05). The improvement rate of JOA scores at final follow-up was 49.2 ± 31.7% in the stable group and 47.1 ± 39.2% in the unstable group (p>0.05). Conclusions: The efficacy of laminoplasty combined with local fusion for unstable cervical spinal cord injury with spinal stenosis was certain. Developmental cervical spinal canal stenosis is the main pathological factor that causes multiple spinal cord compression in the patients with cervical spinal cord injury.